What you need to know about the world. Toward a taxonomy of planetary health knowledge - Franziska Rees; Oliver Wilhelm (Frontiers in Public Health)
Knowledge about the world is deemed a core competence to engage in shifting the world to a better place to live. Although the importance of this knowledge is emphasized in several political and educational frameworks, there is still a lack of a definition of the scope of the required knowledge. Looking for a suitable taxonomy about world knowledge for sustainable development we analyzed different approaches in this area—Sustainable Development Goals, Global Citizenship, and Planetary Health—concluded that none of these approaches satisfied the requirements of a knowledge taxonomy and identified a huge amount of overlapping content among these approaches. By merging these frameworks, we developed the Planetary Health Knowledge (PHK) taxonomy targeting knowledge about the health of the planet, human individuals, human systems, and their interaction. This hierarchical taxonomy exhaustively and disjunctively covers all relevant aspects of PHK in seven domains: Health, Nutrition, Environment, Safety, Education, Standard of Living, and Political and Economic Systems. We further discuss the existence of jingle-jangle fallacies in this field, quality criteria for evaluating taxonomies, and possibilities to use the PHK taxonomy.